Manufacturing method of functional edible charcoal and hydrogen powder

By carbonizing plants with deep sea water or hydrogen-reduced water-soluble silicon-containing water, the adsorption properties of edible charcoal are enhanced, and a hydrogen powder is produced that effectively supports hydrogen adsorption, addressing the limitations of existing products.

JP7655524B2Active Publication Date: 2025-04-02SUMI PLUS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020096027
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-02
Publication Date
2025-04-02
Estimated Expiration
2040-06-02

AI Technical Summary

Technical Problem

Existing edible charcoal and activated carbon products have limited adsorption properties, and there is a need for a method to improve these properties while also developing a hydrogen powder with cosmetic functions that can support a large amount of hydrogen.

Method used

The method involves carbonizing plants at high temperatures and activating them using deep sea water or water-soluble silicon-containing water that has been reduced with hydrogen, thereby enhancing the adsorption properties of the charcoal. Additionally, a hydrogen powder production method is employed, where coral powder is calcined under controlled atmospheric pressure and treated with hydrogen-reduced deep sea water to support hydrogen adsorption.

Benefits of technology

The improved charcoal exhibits enhanced adsorption properties, and the hydrogen powder effectively supports a large amount of hydrogen, demonstrating improved performance compared to existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655524000020
    Figure 0007655524000020
  • Figure 0007655524000021
    Figure 0007655524000021
  • Figure 0007655524000022
    Figure 0007655524000022
Patent Text Reader

Abstract

To improve adsorption properties of charcoal and activated carbon and improve the amount of hydrogen supported on mineral powder.SOLUTION: A method for producing functional edible charcoal having a high adsorption function and being edible includes at least the steps of: setting the atmosphere in a furnace to 1 to 3 atm and carbonizing vegetation including Japanese red pine, bamboo, ume fruits or coconut shells, and Quercus phillyraeoides at 500 to 1,500°C; and causing an activation reaction using "deep sea water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen. A method for producing a hydrogen powder that supplements essential and trace minerals includes at least the steps of: setting the atmosphere in a furnace to 1 to 6 atm and firing a coral powder at 50 to 200°C; and supporting hydrogen using "deep sea water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing "functional edible charcoal" that has a high adsorption function and is used for food, and "high-concentration hydrogen-carrying powder" that contains minerals and is used for beauty purposes. [Background technology]

[0002] Conventionally, edible charcoal suitable for adding to food has been known. For example, Patent Document 1 discloses a method for producing edible charcoal to be added to food. In Patent Document 1, edible charcoal is produced through a smoke treatment process in which naturally dried bamboo is smoked at 50 to 60 ° C to obtain uncarbonized material, a smelting process in which the uncarbonized material is ignited and refined at a kiln temperature of 800 to 1100 ° C to carbonize it, and then slowly cooled to obtain raw material charcoal, a coarse crushing process in which the obtained raw material charcoal is coarsely crushed to obtain powder with a particle size of 2 to 5 mm, and a fine crushing process in which the powder obtained in the coarse crushing process is used to obtain fine powder with a particle size of 10 to 30 μm or 20 to 40 μm using a vibration mill, or a fine powder with a particle size of 0.5 to 9 μm using an airflow jet mill. By using bamboo charcoal fine powder with a particle size of 0.5 to 40 μm as edible charcoal, the texture is not impaired even when it is added to food, and further, since the bamboo charcoal fine powder has a stable product particle size, it is easy to handle.

[0003] Meanwhile, Patent Document 2 discloses a health food containing traditional Indian medical ingredients that enhance the efficacy of suppressing allergic symptoms. This health food is characterized by having the seeds of Kalijiri (scientific name: Vernonia Anthelmintica) as the main ingredient, coral powder, zita bark or marigold (calendula) flower powder as effect enhancers, and one or more of Centella asiatica, sunflower seeds, fennel, grape skin extract, and kelp as effect enhancers, which are then granulated into a dry powder.

[0004] Recently, the idea of ​​"hydrogen medicine," which utilizes the excellent properties of hydrogen from the perspective of preventive medicine, has been gaining popularity. Since harmful active oxygen is the root cause of all kinds of illnesses, it is believed that by ingesting hydrogen on a daily basis and eliminating the harmful active oxygen, the risk of getting sick may be reduced. For this reason, there has been a lot of attention being paid to taking in hydrogen into the body by ingesting hydrogen water or inhaling hydrogen gas.

[0005] Patent Document 3 discloses a technology that uses coral calcium as a negative hydrogen ion releasing substance, and provides this coral calcium for consumption by baking it in two stages, oxidative baking and reduction baking. In this technology, a mixture of coral calcium and wheat flour is molded, and then oxidative baking and reduction baking are performed. The baked product is powdered and made into tablets or capsules to produce negative hydrogen ions (H-) that can be consumed. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2004-121238 A [Patent Document 2] JP 2007-135495 A [Patent Document 3] Patent No. 4404657 specification Summary of the Invention [Problem to be solved by the invention]

[0007] However, there is still room for improvement in the adsorption properties of charcoal and activated charcoal, and it is possible to further improve the adsorption properties. Also, coral is rich in minerals and has functions that are beneficial to the human body, so there is room for making it easier to support (adsorb) hydrogen.

[0008] The present invention has been made in consideration of the above circumstances, and aims to provide a method for producing functional edible charcoal that improves the adsorption properties of charcoal and activated carbon, and a method for producing hydrogen powder using coral powder that can support (adsorb) a large amount of hydrogen. [Means for solving the problem]

[0009] (1) In order to achieve the above object, the present invention has taken the following measures. That is, the method for producing functional edible charcoal of the present invention is a method for producing functional edible charcoal that has a high adsorption function and is edible, and is characterized by including at least a step of setting the pressure in a furnace to 1 to 3 atmospheres and carbonizing vegetation including red pine, bamboo, plum fruit, coconut shells, and phillyraeoides at 500°C to 1500°C, and a step of inducing an activation reaction using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen.

[0010] (2) Furthermore, the method for producing hydrogen powder of the present invention is a method for producing hydrogen powder that supplements essential and trace minerals, and is characterized by including at least the steps of setting the pressure inside a furnace to 1 to 6 atmospheres and firing coral powder at 50°C to 200°C, and causing hydrogen loading (adsorption) using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen.

[0011] (3) The method for producing hydrogen powder of the present invention is characterized in that, instead of the coral powder, a powder impregnated with deep sea water, hydroxyapatite derived from natural living organisms or minerals, deep sea water powder, seaweed powder, weathered shell calcium powder, oyster shell powder, scallop shell powder, pearl shell powder, fine silicon dioxide (silica), and a powder containing essential and trace minerals including at least one of water-soluble silicon (hydrated silica or hydrated silicic acid, such as metasilicic acid or orthosilicic acid) are used. Effect of the Invention

[0012] According to the present invention, the adsorption characteristics are improved and a large amount of hydrogen can be supported (adsorbed). [Brief description of the drawings]

[0013] [Figure 1] 1 is a flowchart showing a manufacturing process of functional edible charcoal according to an embodiment of the present invention. [Diagram 2] 1 is a flowchart showing the manufacturing process of hydrogen-loaded coral powder according to the present embodiment. [Diagram 3] FIG. 1 shows how silicon content in human aorta changes with age. [Figure 4] FIG. 1 shows experimental results showing hydroxyl radical control activity. [Diagram 5] FIG. 1 shows experimental results showing hydroxyl radical control activity. [Figure 6] FIG. 1 shows experimental results showing hydroxyl radical control activity. [Figure 7] FIG. 1 shows the results of a urinary 8-OHdG test. [Figure 8] FIG. 2 is a diagram showing the results of a "Red No. 2 adsorption test" for the Super Cleanse activated carbon according to this embodiment. [Figure 9] FIG. 2 is a diagram showing the results of a "malodor adsorption test" for the Super Cleanse activated carbon according to the present embodiment. [Figure 10] FIG. 2 is a diagram showing the results of a "food oil and fat adsorption test" for the Super Cleanse activated carbon of this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In this specification, the functional edible carbon is referred to as "Super Cleanse activated carbon". The method for producing Super Cleanse activated carbon according to this embodiment is characterized by at least including a step of carbonizing vegetation including red pine, bamboo, plum fruit, coconut shell, and Ubamegashi at 500°C to 1500°C by setting the pressure in the furnace to 1 atm to 3 atm, and a step of causing an activation reaction using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen. In addition, in this specification, the hydrogen powder according to this embodiment is referred to as "reduced mineral hydrogen powder". The method for producing reduced mineral hydrogen powder according to this embodiment is characterized by at least including a step of setting the pressure in the furnace to 1 atm to 6 atm, burning coral powder at 50°C to 200°C, and a step of causing an activation reaction using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen. As described above, this embodiment is characterized in that the activation reaction is caused by using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen.

[0015] Deep ocean water is generally understood to be seawater at a depth of 200m or more, and has the characteristics of cleanliness, abundance of inorganic nutrients, and low temperature stability compared to surface water. In other words, deep ocean water is not affected by river water polluted by human wastewater, so it is not contaminated by chemicals, and since plankton cannot grow because sunlight does not reach it, the amount of harmful bacteria is less than one thousandth of that of surface water. In addition, compared to surface water, it is rich in inorganic nutrients necessary for the growth of phytoplankton, and furthermore, it has the characteristics that the water temperature and contained components are less likely to change, and the water quality is stable. Since the Super Cleanse activated carbon and reduced mineral hydrogen powder of this embodiment use deep ocean water that has been reduced by hydrogen, it is considered that the treatment can be performed in a state where the ionization of minerals such as calcium and magnesium is promoted.

[0016] The inventors conducted a test on the ability of "deep ocean water that has been subjected to reduction processing using hydrogen" (sometimes referred to as "super-concentrated solution of reduced minerals") to eliminate alcohol and acetaldehyde. The equipment used was a "Gas Chromatograph GC-2010AF / AOC: manufactured by Shimadzu Corporation," and the reagents used were "whisky (Suntory Kakubin)" and "acetaldehyde (manufactured by Wako Pure Chemical Industries, Ltd.)." The test method was as follows.

[0017] [About alcohol] (a) Three drops of the sample were added to 100 ml of whiskey concentrate (40% alcohol), stirred, and then the alcohol content was measured after leaving it to stand for two hours. (b) Six drops of the sample were added to 100 ml of whiskey concentrate (40% alcohol), stirred, and then allowed to stand for two hours before measuring the alcohol content.

[0018] [About acetaldehyde] (a) Dilute acetaldehyde (90%) 100 times to make a 0.9% solution. (b) Three drops of the sample were added to 100 ml of (a) above, stirred, and the acetaldehyde concentration was measured after 30 minutes. (c) Six drops of the sample were added to 100 ml of (a) above, stirred, and the acetaldehyde concentration was measured after 30 minutes.

[0019] The results are as shown in the following table. [Table 1]

[0020] In this way, it was confirmed that the "deep ocean water that has been subjected to reduction processing using hydrogen" according to this embodiment exhibits the function of eliminating alcohol and acetaldehyde. Acetaldehyde is known to be a bad substance that causes hangovers and bad hangovers and is involved in "oxidation and glycation of the body." The "deep ocean water that has been subjected to reduction processing using hydrogen (reduced mineral concentrated solution)" according to this embodiment has high acetaldehyde elimination activity, and is therefore expected to suppress oxidation and glycation of the body.

[0021] As described above, by processing deep sea water with hydrogen, it is possible to efficiently produce hydrogen gas and / or hydrogen ions carrying electrons by processing the water with hydrogen, and to make them remain dissolved in the water for a long time. Regarding this "electron-carrying hydrogen ion," while a typical hydrogen ion is "H+" that is missing one electron, there is a "negative hydrogen ion H-" that is charged with two electrons, and it has been reported that research toward practical use is being conducted at Kyoto University and Tokyo Institute of Technology. If you drink or eat the reduced mineral hydrogen powder (calcined coral calcium hydrogen powder) using the "deep sea water that has been reduced with hydrogen" according to this embodiment, you can expect to efficiently deliver hydrogen to the stomach, intestines, liver, and blood. By applying it to the skin or scalp, hydrogen can be efficiently delivered to cells that are directly related to beauty.

[0022] Next, we will explain silicon and its related substances. Here, based on the International Atomic Weight Table (2010), the atomic weights are "Si 28.0855", "H 1.00794", and "O 15.9994", rounded off to the third decimal place. Silicon is represented by "Si" and has an atomic weight of 28.09. The amount of silicon required by the human body per day is "10 to 40 mg", and the recommended intake amount for silicon is used. Next, silica is also called silicon dioxide, represented by "SiO2", and has a molecular weight of 60.09 (28.09 + 16.00 x 2 = 60.09). Although it is anhydrous and not water-soluble silicon, it is sometimes called "silica" as an alternative name for water-soluble silicon because the word "silica" sounds good. However, water-soluble silicon (hydrated silica / hydrated silicic acid such as metasilicic acid or orthosilicic acid) and silica (silicon dioxide) are different substances, as shown in the molecular formula and molecular weight below. Silica (silicon dioxide) hydrates and one H2O is added to turn it into metasilicic acid, and it hydrates further and one H2O is added to turn it into orthosilicic acid, which is easily absorbed by the body and used effectively. Water-soluble silicon is hydrated silica (hydrated silicic acid), a substance that takes the form of metasilicic acid or orthosilicic acid. Insoluble silica (silicon dioxide) that makes up mountains and rocks combines with water and H2O to dissolve and turn into metasilicic acid. It hydrates further (adds H2O) and turns into orthosilicic acid, which is more easily absorbed by the body, and reaches the ocean, where it is absorbed by phytoplankton (diatoms) at the bottom of the food chain, and is used by the body. To repeat, "drinkable silica (silicon) derived from hot springs and spring water" sold as mineral water refers to the inclusion of "soluble silicon" (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid) that has dissolved from rocks (silica, silicon dioxide, silicic acid, and anhydrous silicic acid) and has long been used as a skin-beautifying ingredient in drinking spring water. By the way, "silicon / silica" = "28.09 / 60.09" = "0.47" times. Also, "silica / silicon" = "60.09 / 28.09" = "2.14" times, so silica (silicon dioxide, SiO2) = silicon (Si) x 1 / 0.47 = silicon (Si) x 2.14 (based on the conversion value used by the Japan Food Analysis Center).

[0023] As a hydrogen carrier, fine silicon dioxide SiO2 has a structure in which two oxygen atoms O are bonded to silicon Si, and due to its adsorption properties, it is expected to hold hydrogen and extend the time that dissolved hydrogen is retained. In addition, in the case of water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid), orthosilicic acid Si(OH)4 has a structure in which four hydroxyl groups OH are bonded to silicon Si, and it is expected to hold dissolved hydrogen more strongly.

[0024] Next, metasilicic acid is expressed as "H2SiO3" and has a molecular weight of 78.1 (1 x 2 + 28.09 + 16.00 x 3 = 30.09 + 48.0 = 78.09). From this, it can be said that metasilicic acid is formed when silica (silicic acid, silicon dioxide) is hydrated and changed into "H2O + SiO2 = H2SiO3".

[0025] In addition, the following relationship is found: "Silicon / Metasilicic acid" = "28.09 / 78.09" = "0.36" times "Metasilicic acid / silicon" = "78.09 / 28.09" = "2.78" times "Silica / Metasilicic Acid" = "60.09 / 78.09" = "0.77" times "Metasilicic acid / silica" = "78.09 / 60.09" = "1.30" times

[0026] Next, orthosilicic acid is expressed as "H4SiO4" and its molecular weight is 78.1 (1 x 4 + 28.09 + 16.00 x 4 = 32.09 + 64.0 = 96.09). Compared to the molecular formula of metasilicic acid above, it has an additional "H2O" added to it, making it hydrated. Water-soluble silicon is ultimately "orthosilicic acid (H4S i Orthosilicic acid exists in the form of "H4SiO4" and its biogeochemical cycle is controlled by diatoms. This "orthosilicic acid (H4SiO4)" is "Si(OH)4" and has a "beautiful molecular structure with four OH groups clasping hands" with Si at the center, making it highly absorbent. In addition, the following relationship is found: "Silicon / orthosilicic acid" = "28.09 / 96.09" = "0.29" times "Orthosilicic acid / silicon" = "96.09 / 28.09" = "3.42" times "Silica / orthosilicic acid" = "60.09 / 96.09" = "0.63" times "Orthosilicic acid / silica" = "96.09 / 60.09" = "1.60" times

[0027] Here, we will explain the recommended daily intake. As mentioned above, "silica / silicon" = "60.09 / 28.09" = "2.14" times, "metasilic acid / silicon" = "78.09 / 28.09" = "2.78" times, "orthosilicate / silicon" = "96.09 / 28.09" = "3.42" times. Since the recommended daily intake of silicon alone is "10 to 40 mg", the recommended daily intake when converted to silica, metasilicic acid, and orthosilicate is considered to be within the range of each conversion value from the silicon amount. In other words, the amount of "silicon" that makes up water-soluble silicon is "10 to 40 mg," the amount of "silica" that makes up water-soluble silicon is "21.4 to 85.6 mg (10 to 40 mg x 2.14 times)," the amount of metasilicic acid, which is water-soluble silicon, is "27.8 to 111.2 mg (10 to 40 mg x 2.78 times)," and the amount of orthosilicic acid, which is water-soluble silicon, is "34.2 to 136.8 mg (10 to 40 mg x 3.42 times)."

[0028] According to the paper "Biochemistry of Silicon and Related Problems (Nobel Foundation Symposia)" edited by "Gerd Bendz," "the silicon content in the human aorta changes with age." As shown in Figure 3, if the amount of water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid) in the body at birth is taken as 100, ignoring individual differences, it will decrease to about half by the age of 40. Since humans cannot produce the necessary water-soluble silicon in their own bodies, it is important to actively ingest water-soluble silicon in order to maintain beauty and health.

[0029] Water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid) is also found in the human body, and is present in hair, nails, blood vessels, bones, teeth, joints, cell walls, etc. Water-soluble silicon in the body has the effect of binding collagen, and is useful for regenerating, strengthening, and maintaining bones, teeth, hair, nails, and collagen, as well as affecting skin moisturization. Water-soluble silicon is also found in the skin (dermis layer), hair, nails, etc., and binds collagen, ceramide, elastin, hyaluronic acid, chondroitin, etc., maintaining the firmness and elasticity of the skin and binding and strengthening tissues. Furthermore, it is known that excellent beauty and health effects can be obtained by combining ceramide or hyaluronic acid, lactic acid bacteria, and water-soluble silicon. That is, ceramide enhances the barrier function of the skin (especially the moisturizing effect) and has the function of suppressing the evaporation of moisture from the epidermis, hyaluronic acid enhances the water retention function of the skin and prevents dryness, lactic acid bacteria have an intestinal regulation effect as well as an immune-boosting function and an anti-allergic function, and water-soluble silicon promotes the synthesis of collagen in the skin and has the function of bonding and improving the quality of collagen layers, so it is expected that the combination of these will produce beauty and health effects. Furthermore, water-soluble silicon is absorbed through the intestinal wall and has the effect of solubilizing adhesions inside the blood vessels when passing through the blood vessels, and is also effective in preventing arteriosclerosis. Furthermore, it has the function of promoting plant growth or strengthening stems.

[0030] The Framingham Offspring Study in the United States found that there is a close relationship between silicon intake (contained in water-soluble silicon) and bone mineral density (BMD). In this study, 2,846 male and female study subjects in their 30s to 80s were divided into four groups according to the results of their silicon intake and compared. As a result, it was found that the higher the silicon intake, the higher the femoral neck bone density in men and premenopausal women. This suggests that silicon is effective in preventing osteoporosis. Since the importance of silicon has been revealed, dietary supplements and supplements containing water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid), which is easily absorbed by the body, have been attracting attention in Europe and the United States for quite some time, and the market for silicon products in Europe and the United States is already very large. Human bones are composed of about 70% hydroxyapatite and about 30% collagen, and water-soluble silicon is what runs through them and makes them strong as tissue. For this reason, it is expected that the combination of water-soluble silicon, hydroxyapatite, and collagen will have a significant synergistic effect.

[0031] Both plant-derived and mineral-derived silicic acid can be processed with deep seawater under the same temperature and pressure conditions to obtain water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid). However, the balance of minerals other than silicon contained in each is different, so if you want to enjoy both the blessings of the earth and the blessings of plants, you can expect a synergistic effect by mixing concentrated solutions of plant-derived water-soluble silicon and mineral-derived water-soluble silicon. In addition to bamboo, you can also use plants with a high silicon content, such as rice (rice straw and rice husk), bamboo grass, millet, Japanese silver grass, sugar cane, and wheat, as well as horsetail and horsetail. Mineral-derived silicic acid such as quartz and quartz can also be used. Silica derived from natural water or hot spring water from Kirishima (Kirishima Mountain Range) or Hakone can also be used. In addition, by utilizing silicic acid dissolved from Mt. Fuji lava marimo powder, or by combining it with silicic acid abundantly contained in spring water and hot spring water of Mt. Fuji, further synergistic effects of minerals contained other than silicic acid can be expected. "The blessings of minerals from Mt. Fuji" and "the blessings of deep sea water minerals" are exactly the blessings of high and low minerals, and can be said to be the blessings of yin and yang mineral balance. In addition, "vanadium" is contained in the spring water, hot spring water, lava, etc. of Mt. Fuji, and "vanadium" is known to be effective against diabetes. In this embodiment, too, by containing "vanadium", it is possible to expect an effect against diabetes.

[0032] Mineral waters rich in water-soluble silicon (hydrated silica / hydrated silicic acid such as metasilicic acid or orthosilicate) are mainly distributed in the Fuji and Hakone regions and Kyushu region. Kyushu region has world-class volcanoes and hot springs such as Aso, Unzen, Kirishima, Kuju, Sakurajima, and Beppu, and it is known that the strata in this area contain a lot of silicic acid, which over a long period of time changes into water-soluble silicon (hydrated silica / hydrated silicic acid such as metasilicic acid or orthosilicate) and dissolves into the water. Regarding the hot spring water of Kirishima, which is rich in water-soluble silicon, there is a myth that "long ago, Izanagi-no-Mikoto and Izanami-no-Mikoto took Hiruko-no-Mikoto, who could not stand, on a boat and had him undergo hot spring treatment at the "Nageki-no-Mori" (Forest of Lamentations) where they arrived." In this embodiment, silicic acid derived from spring water or natural water of Kirishima or Sakurajima may also be used.

[0033] [First embodiment] Next, the manufacturing method of the Super Cleanse activated carbon according to this embodiment will be described. FIG. 1 is a flow chart showing the manufacturing process of the Super Cleanse activated carbon according to this embodiment. First, vegetation including red pine, bamboo, plum fruit or coconut shell, and Quercus phillyraeoides is harvested (step S1), and the harvested vegetation is heat-treated in a charcoal kiln (step S2). This heat treatment is "carbonization", and the treatment conditions are, for example, an atmospheric pressure of 1 to 3 atmospheres in the furnace and a temperature of 500°C to 1500°C. Next, an activation reaction is caused using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen (step S3). In this way, when the carbonized raw material (charcoal from plants including red pine, bamboo, plum fruit, coconut shells, and phillyraeoides) is reacted with mineral-containing water (deep ocean water or water-soluble silicon-containing water that has been reduced with hydrogen) at temperatures between 500°C and 1500°C, the partial reaction between the carbon and minerals creates micropores (diameter 5-200 angstroms), producing activated carbon. This improves the adsorption properties of Super Cleanse activated carbon. Since the atmospheric pressure and temperature conditions are not uniform and the size of the xylem varies depending on the plant, it is necessary to find the optimal conditions for each plant and carbonize it.

[0034] [Verification example 1] Here, the inventors conducted a test to prove that Super Cleanse activated carbon has a low abrasive effect on teeth, since it is characterized by being carbonized to a "soft and fluffy" texture using reduced water in addition to temperature and pressure. Since the hardness of glass surfaces is weaker than tooth enamel, an abrasive effect test was conducted on the glass surface using an electric toothbrush and "Ina Akamatsu Tao Charcoal / Coconut Shell Activated Carbon Granules (Dispersed Processing)". The result was that the glass surface was not scratched at all, even after brushing with an electric toothbrush for an hour with charcoal. This demonstrated that the abrasive effect of Super Cleanse activated carbon on teeth is completely ok.

[0035] In addition, in this embodiment, the activation reaction may be performed not only using deep sea water, but also using reduced water that has been hydrogen-processed from "spring water or hot spring water from Fuji, the Southern Alps, the Central Alps, Kirishima natural water, etc., which has been passed through an activated carbon filter to concentrate minerals."

[0036] [Verification example 2] In addition, the inventors conducted a "Red No. 2 adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Kamakura quartz bamboo charcoal powder, Ina Akamatsu Myo charcoal powder), other companies' activated carbon powder with a medical track record, and bamboo charcoal powder (domestically produced). The test method was to add a sample to water colored with Red No. 2 (amaranth), stir it, and then filter it to measure the absorbance. The results are shown in the following table and Figure 8. [Table 2] The "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal)" according to this embodiment is uniquely processed using minerals under high temperature and pressure, so fine pores are formed deep inside. Therefore, it has been found that an extremely high adsorption rate (90% or more) is achieved compared to commercially available activated carbon and bamboo charcoal powder (domestically produced).

[0037] [Verification example 3] The inventors also conducted an "odor adsorption test" using functional coconut shell activated carbon as the Super Cleanse activated carbon according to this embodiment through a public third-party organization. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder). The test method was as follows: (1) a Tedlar bag (smell bag: 3L) containing a test specimen was used as a "sample measurement", and one without the test specimen was used as a "blank test", and (2) 10 types of odor components were added to both, and the odor was measured after leaving them for 30 minutes. Each sample was measured three times, and the average value was used as the result. Here, the adsorption rate (%) is synonymous with the reduction rate (%), and is obtained by dividing (concentration of blank test)-(concentration of data measurement) by (concentration of blank test) and multiplying by 100. The results are shown in the following table and Figure 9. In the following table, "ammonia" has a unique strong irritating odor, and "acetic acid" has a strong sour taste and irritating odor. "Methyl mercaptan" is a typical breath odor substance produced by the periodontal disease bacteria Porphyromonas gingivalis, and "hydrogen sulfide" has a rotten egg odor. "Acetaldehyde" has a unique odor and is an air pollutant that comes from automobile exhaust and cigarette smoke. "Pyridine" has an odor similar to rotten fish, and "trimethylamine" is the main cause of the fishy smell of fish. "Nonenal" has an oily, grassy odor, and its relationship with the odor of aging is being studied. "Indole" has a feces odor, and "isovaleric acid" has an unpleasant, pungent odor similar to the odor of cheese or sweat, feet, or bad breath caused by aging. [Table 3] As such, "Super Cleanse Activated Carbon (functional coconut shell activated carbon)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and has been shown to have an extremely high adsorption rate for many types of unpleasant odors.

[0038] [Verification example 4] In addition, the inventors conducted a "food fat adsorption test" using functional coconut shell activated carbon as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test samples were Super Cleanse activated carbon (functional coconut shell activated carbon powder), coconut shell activated carbon powder (made in China), and commercially available bamboo charcoal powder (made in Japan). The test method was as follows: (1) add food fat to hot water and stir until homogenous, (2) add a sample and stir for 10 minutes, (3) filter this and measure it. (4) Add food fat to the same amount of hot water as (1), stir and filter the mixture, and compare it with the original solution. The results are shown in the following table and Figure 10. [Table 4] The "Super Cleanse Activated Carbon (functional coconut shell activated carbon)" according to this embodiment is uniquely processed using minerals under high temperature and pressure, which creates fine pores deep inside, and compared to coconut shell activated carbon powder (made in China) and commercially available bamboo charcoal powder (made in Japan), it has an extremely high carbon ratio (98% or more). Due to this composition, a third-party organization conducted a test to confirm that 1 g of charcoal powder adsorbs 5.6 g of food oil.

[0039] [Verification example 5] The inventors also conducted a "heavy metal adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Tao charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Tao charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) dilute the cadmium standard solution, lead standard solution, and mercury standard solution, (2) add the test specimen to these diluted solutions, stir, and then filter the solution, which was then analyzed using an ICP (inductively coupled plasma) optical emission spectrometer. The adsorption rates are shown in the table below. [Table 5] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and an extremely high adsorption rate for three types of heavy metals has been confirmed.

[0040] [Verification example 6] In addition, the inventors conducted a "nicotine adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was (1) diluting the nicotine standard solution, (2) adding the test specimen to these solutions, stirring, and then filtering the solution, which was then analyzed by GC-MS (gas chromatograph mass spectrometer). The adsorption rate is as shown in the table below. [Table 6] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and an extremely high adsorption rate for nicotine has been confirmed.

[0041] [Verification example 7] In addition, the inventors conducted an "indole / skatole adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was (1) dissolving indole and skatole, which emit fecal odor, (2) adding the test specimen to these solutions, stirring for 10 minutes, and then filtering the solution, which was then analyzed by GC-MS (gas chromatograph mass spectrometer). The adsorption rate is as shown in the table below. [Table 7] As such, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" undergoes a unique process that utilizes minerals under high temperature and pressure, which creates tiny pores deep inside, and an extremely high adsorption rate for indole and skatole has been confirmed.

[0042] [Verification example 8] The inventors also conducted a "tobacco tar dye adsorption test" through a third-party research institute using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) commercially available tobacco leaves were placed in a beaker and boiled in hot water to prepare a stock solution, and (2) the test specimen was added to the stock solution, which was stirred and then filtered, and the absorbance was measured. The adsorption rates are as shown in the table below. [Table 8] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and an extremely high adsorption rate for tobacco tar dyes has been confirmed.

[0043] [Verification example 9] The inventors also conducted an "edible dye adsorption test" through a third-party research institute using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method involved adding the test specimen to water colored with an edible dye, stirring, and then filtering the mixture to measure the absorbance. The adsorption rates are shown in the table below. [Table 9] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and an extremely high adsorption rate for food coloring has been confirmed.

[0044] [Verification example 10] The inventors also conducted a "trihalomethane (chloroform) adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) prepare a chloroform solution, (2) place the sample in a chromatographic tube in a layer, gently pour the solution (1) from above, and (3) analyze the permeated liquid using a GC-MS (gas chromatograph mass spectrometer). The adsorption rates are as shown in the table below. [Table 10] Thus, all test samples were confirmed to have very good trihalomethane adsorption. The standard value for trihalomethane in tap water is 0.1 ppm, but in this test, sufficient adsorption was confirmed even when the concentration was 200 times the standard value. Depending on the heating conditions, the trihalomethane in tap water may increase, but it is estimated that the Super Cleanse activated carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal) of this embodiment can adequately adsorb it.

[0045] [Verification example 11] The inventors also conducted a "residual chlorine adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) dilute sodium hypochlorite, (2) place filter paper on a funnel, put the test specimen in, pour 100 ml of the diluted solution (2) from above, and (3) measure the permeated liquid by backtest. The diluted solution (1) was permeated through the filter paper as a filter paper blank and measured. The adsorption rate is as shown in the table below. [Table 11] Thus, in all test samples, no residual chlorine was detected after the adsorption treatment, and the adsorption of residual chlorine was very good. The standard value for residual chlorine in tap water is 0.1 ppm, but in this test, sufficient adsorption was confirmed even when the concentration was 50 times the standard value.

[0046] [Verification example 12] The inventors also conducted an "arsenic adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) dilute the arsenic standard solution, (2) add the test specimen to the diluted solution prepared in (1), stir with a magnetic stirrer, (3) filter with Advantec 2B filter paper, and (4) measure the arsenic concentration. The adsorption rate is as shown in the table below. [Table 12] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and a high adsorption rate for arsenic has been confirmed.

[0047] [Verification example 13] The inventors also conducted an "aluminum adsorption test" through a third-party research institute using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) dilute the aluminum standard solution, (2) add the test specimen to the diluted solution prepared in (1), stir, and filter the solution, which was then analyzed using an ICP (inductively coupled plasma) optical emission spectrometer. The adsorption rates are shown in the table below. [Table 13] In this way, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, and a high adsorption rate for aluminum was confirmed, especially for Ina Akamatsu Myo charcoal.

[0048] [Verification example 14] In addition, the inventors conducted a "bacteria adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Tao charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Tao charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method used oral bacteria from a man suspected of having periodontal disease: (1) saliva, which was the bacterial solution used, was diluted 10-fold with saline, then filtered using filter paper (Advantec filter paper No. 2); (2) 1 g of the specimen was added to 10 ml and mixed for 3 minutes; (3) After waiting for charcoal to settle, 1 ml of the supernatant was taken, diluted, and inoculated into a culture medium. The results are as follows: [Table 14] As such, it has been revealed that "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Quartz Bamboo Charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, enabling it to adsorb oral bacteria with an adsorption rate of nearly 100%.

[0049] [Verification example 15] The inventors also conducted an "AGEs adsorption test" through a third-party research institute using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method was as follows: (1) alanine and glucose were dissolved in water and heated, and after natural cooling, a diluted AGEs solution was prepared; (2) each test specimen was added to the AGEs solution, which was stirred and then filtered, and the absorbance was measured. The results are as follows: [Table 15]

[0050] As described above, "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal)" is uniquely processed using minerals under high temperature and pressure, which creates fine pores deep inside, and it was revealed that functional coconut shell activated carbon in particular can adsorb AGEs with an adsorption rate close to 100%. In addition, while commercially available charcoal products (1) and (2) are edible charcoal ingredients that boast high price range and high functionality, the superiority of "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, Kamakura quartz bamboo charcoal)" was clear even when compared to these. Furthermore, as mentioned above, the AGEs adsorption test results were 100% for functional coconut shell activated carbon, and even if the error was taken into account, the results were close to 100%, while Ina Akamatsu Myo Charcoal was 56%, Kamakura Keichiku Charcoal was 51%, and the spherical activated carbon prescription drug (fine grain sachet) was 17%. Therefore, functional coconut shell activated carbon showed a high adsorption rate of 5.9 times that of this prescription drug, Ina Akamatsu Myo Charcoal was 3.3 times that of this prescription drug, and Kamakura Keichiku Charcoal was 3.0 times that of this prescription drug. This clearly shows the superiority of "Super Cleanse Activated Carbon (functional coconut shell activated carbon, Ina Akamatsu Myo Charcoal, Kamakura Keichiku Charcoal)" over this prescription drug.

[0051] [Verification example 16] In addition, the inventors conducted a "purine adsorption test" using functional coconut shell activated carbon, Ina Akamatsu Myo charcoal, and Kamakura quartz bamboo charcoal as the Super Cleanse activated carbon according to this embodiment through a third-party research institute. The test specimen was Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder, and Kamakura quartz bamboo charcoal powder). The test method used "adenine" as the purine, added 1 g of the charcoal sample to a solution of 50 ppm purine concentration of general beer, stirred, filtered using filter paper, and measured the concentration by liquid chromatography. The measurement results are as follows. The measurement results are as follows. [Table 16]

[0052] As such, it has become clear that "Super Cleanse Activated Charcoal (functional coconut shell activated carbon powder, Ina Akamatsu Myo Charcoal Powder, Kamakura Quartz Bamboo Charcoal Powder)" is uniquely processed using minerals under high temperature and pressure, which creates tiny pores deep inside, allowing it to adsorb purines with a high adsorption rate.

[0053] [Verification example 17] An "acrylamide adsorption test" was conducted using the Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder) according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder). The test method involved adding each specimen to an aqueous acrylamide solution, stirring and centrifuging, and filtering the supernatant through a filter. The concentration of the filtrate was measured using a "TOC-V CSN (total organic carbon meter)", with the following results:

[0054] [Table 17]

[0055] It has been revealed that the Super Cleanse activated carbon (functional coconut shell activated carbon powder, Ina Akamatsu Myo charcoal powder) according to this embodiment can adsorb acrylamide at a high adsorption rate. In particular, the functional coconut shell activated carbon powder showed an adsorption rate of over 90%. Acrylamide is contained in instant coffee and potato chips and is known to be a harmful substance that is carcinogenic, but by using the Super Cleanse activated carbon according to this embodiment, a high percentage of acrylamide can be removed.

[0056] [Verification example 18] Next, a caffeine adsorption test was conducted on the Super Cleanse activated carbon (functional coconut shell activated carbon powder, Kishu Bincho activated carbon powder) according to this embodiment. The test specimens were Super Cleanse activated carbon (functional coconut shell activated carbon powder, Kishu Bincho activated carbon powder). The test method was to add the specimens to a caffeine aqueous solution, stir, filter with filter paper, and measure the concentration by liquid chromatography. The results are shown in the following table.

[0057] [Table 18] Thus, both Super Cleanse activated carbon (functional coconut shell activated carbon powder and Kishu Bincho activated carbon powder) showed high caffeine adsorption rates. Caffeine is said to have the effect of revitalizing the body when consumed in moderate amounts, but drinking large amounts has side effects, so coffee from which the caffeine has been removed is called decaffeinated and has been attracting attention. By using the Super Cleanse activated carbon of this embodiment, it is possible to remove a high percentage of caffeine.

[0058] [Second embodiment] Next, a manufacturing method of the reduced mineral hydrogen powder according to this embodiment will be described. FIG. 2 is a flow chart showing the manufacturing process of the reduced mineral hydrogen powder according to this embodiment. This reduced mineral hydrogen powder is capable of generating hydrogen at a high concentration and for a long time. First, coral powder is supplied into a furnace (step T1), and the coral powder is heat-treated in a kiln (step T2). This is a calcination process of the coral, and the processing conditions are that the pressure in the furnace is 1 atm to 6 atm, and the temperature is 50°C to 200°C. Next, hydrogen is carried by using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen (step T3). In this way, when the calcined coral powder and the mineral-containing water ("deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen) are reacted at 1 atm to 6 atm and at a temperature of 50°C to 200°C, micropores (diameter 10 to 200A) are generated by the partial reaction between the coral powder and the mineral. This allows a lot of hydrogen to be carried (adsorbed) by the mineral in the micropores.

[0059] [Verification example 19] The inventors requested a third-party organization (Japan Hydrogen Water Promotion Association) to measure the amount of dissolved hydrogen in the reduced mineral hydrogen powder (calcined coral calcium hydrogen powder) according to this embodiment. As a result, the amount of dissolved hydrogen (redox method) was measured as 840 ppb after 10 minutes, 1,096 ppb after 2 hours, 1,085 ppb after 6 hours, and 1,045 ppb after 24 hours. In addition, a survey of the amount of hydrogen ions generated (conducted by a third-party research organization) was conducted at the "Shiga Prefecture Northeast Industrial Technology Center" using an ultraviolet-visible-near infrared spectrophotometer. The measurement principle is to measure NADH generated by the reaction with the NAD reagent in the presence of hydrogen, and calculate the amount of hydrogen. 10 ml of distilled water was added to 1 g of sample, stirred, and left to stand for 1 hour, and the supernatant was analyzed. As a result, it was found that the amount of hydrogen ions produced from 1 gram of powder was 3.55 x 10 to the power of 20 (3.55 sextillion), which is a level that can supply 5.7 million hydrogen ions per cell for each of the 60 trillion cells in the human body.

[0060] In this way, it was confirmed that hydrogen remains dissolved for a long time, and a large amount of hydrogen ions was generated, so it can be expected that the oral composition according to this embodiment (calcined coral calcium hydrogen powder) will approach the intestines and liver. It is said that about 90% of the active oxygen in the body is generated in the intestines, and the liver is the largest detoxification organ in the body and is constantly exposed to active oxygen. The fact that it is possible to approach both organs shows the potential of hydrogen power.

[0061] Furthermore, the acetaldehyde elimination ability was also investigated using an ultraviolet-visible-near infrared spectrophotometer at the Shiga Prefecture Northeast Industrial Technology Center (conducted by a third-party research institute). The test involved adding 0.2g of sample (calcined coral calcium hydrogen powder) to 200ml of shochu and stirring for 15 minutes. After leaving it to stand, the supernatant was analyzed. As a result, the aldehyde concentration went from 10mg / l to 1.9mg / l, confirming an 81% elimination rate. The fact that it eliminates acetaldehyde, which is said to be the cause of hangovers, is expected to be effective in preventing hangovers and improving liver health.

[0062] [Verification example 20] The present inventors requested a third-party research institute to verify the hydroxyl radical scavenging function of the reduced mineral hydrogen powder (calcined coral calcium hydrogen powder) according to this embodiment. The verification method is as follows. Since it is usually taken at 420mg to 820mg / 100ml, the calcined coral calcium hydrogen powder was suspended in distilled water (32.8mg / ml) and left to stand for about 1 hour to make a stock solution. In the measurement, (1) a 10-fold diluted solution of the stock solution and (2) a stock solution were prepared and finally added to the active oxygen production system to make a 40-fold and 4-fold diluted solution (concentration for drinking), respectively. Regarding the "hydroxyl radical production method," hydrogen peroxide was produced by irradiating it with ultraviolet light.

[0063] Next, the prepared sample was collected in an ESR flat cell, and ESR measurements were performed under the following measurement conditions. Center Field: 335mT Modulation Width: 100μT Sweep Width: ±5.0mT Time Constant: 0.1sec Sweep Time: 1 min Gain: 50

[0064] Next, DMPO was used as a hydroxyl radical scavenger, and the hydroxyl radical scavenging activity of the samples was measured according to the following protocol. Distilled water (control), solution (1) or (2): 50 μL 5.7M DMPO: 20μL 2.5 mM H2O2: 130 μL After irradiating with ultraviolet light for 30 seconds, the ESR was measured.

[0065] In Figure 4, the signal intensity of the ESR spin adducts enclosed in a square was evaluated as "% of control" with the control set at 100%. The signal intensity of the spin adducts was evaluated as "% of control" with the external standard sample Mn 2+ The analysis was performed based on the ratio of the ESR signal (left side of Figure 4) to the ESR signal. Statistical processing was then performed using the individual data. The number of data for each condition was 2 or 3, and statistical processing was performed using Tukey's analysis of variance, with a significance level of 5% or less.

[0066] The results showing the hydroxyl radical scavenging activity are shown in Figures 4 to 6. That is, compared to the control (Figure 4, a), both sample (1) at 0.82 mg / mL (Figure 4, b) and sample (2) at 8.2 mg / mL (Figure 4, c) showed significant hydroxyl radical scavenging (p < 0.05, Tukey multiple test).

[0067] In addition, in this embodiment, instead of coral powder, it is also possible to use powder impregnated with deep sea water, hydroxyapatite derived from natural living organisms or minerals, deep sea water powder, seaweed powder, weathered shell calcium powder, oyster shell powder, scallop shell powder, pearl shell powder, fine silicon dioxide (silica), and powder containing essential and trace minerals including at least one of water-soluble silicon (hydrated silica and hydrated silicic acid such as metasilicic acid or orthosilicic acid). This makes it possible to produce reduced mineral hydrogen powder rich in minerals. By impregnating with deep sea water, hydrogen can be carried (adsorbed) by low-temperature, high-pressure processing on a wide variety of powdered raw materials such as collagen and lactic acid bacteria raw materials.

[0068] [Verification example 21] As mentioned above, instead of coral powder, "powder impregnated with deep sea water, and reduced mineral hydrogen powder containing hydroxyapatite and fine silicon dioxide (silica)" can be produced. The amount of dissolved hydrogen and redox potential of this "silk powder impregnated with deep sea water, pearl oyster-derived hydroxyapatite, and fine silicon dioxide (trademark application pending)" were measured. The test method used a "Trustrex Co., Ltd. ENH-2000" dissolved hydrogen meter and a "Sato Shoji Co., Ltd. YK-23RP-ADV" redox potential meter. 1g of "silk hydrogen pearl powder" was added to 100mL of Yokohama City tap water, stirred, and measured. The results are as follows. In the following description, for convenience, negative values ​​are marked with "▲". (Initial value) Dissolved hydrogen content: 0ppb Oxidation-reduction potential: +600mV pH 7 (10 minutes later) Dissolved hydrogen content: 1312ppb Oxidation-reduction potential: ▲725mV pH 10.81 (1 hour later) Dissolved hydrogen content: 1827ppb Oxidation-reduction potential: ▲906mV pH 10.83 (12 hours later) Dissolved hydrogen content: 1847ppb Oxidation-reduction potential: ▲920mV pH 10.66 (20 hours later) Dissolved hydrogen content: 1730ppb Oxidation-reduction potential: ▲888mV pH 10.12 (32 hours later) Dissolved hydrogen content: 908ppb Oxidation-reduction potential: ▲357mV pH 8.51 (45 hours later) Dissolved hydrogen content: 552ppb Oxidation-reduction potential: ▲182mV pH 8.30 (After 60 hours) Dissolved hydrogen content: 336ppb Oxidation-reduction potential: ▲46mV pH 8.36 (66 hours later) Dissolved hydrogen content: 220ppb Oxidation-reduction potential: ▲14mV pH 8.16

[0069] As shown above, the amount of dissolved hydrogen after 12 hours was 1847ppb. This means that even after 12 hours, the hydrogen content is still 2.3 to 4.6 times that of commercially available hydrogen water at the time of shipment. In addition, the redox potential after 12 hours was -920mV. This shows that "Silk Hydrogen Pearl Powder" effectively removes active oxygen and has high antioxidant properties.

[0070] [Verification example 22] The amount of hydrogen generated from the "silk hydrogen pearl powder" according to this embodiment was quantified. The test method was to measure the amount of hydrogen generated from the "silk hydrogen pearl powder" according to this embodiment by gas chromatography. Specifically, after the "first silk hydrogen pearl powder" and the "second silk hydrogen pearl powder" according to this embodiment were crushed in a mortar, 5 mg and 2 mg were taken and added to a 125 mL vial, 25 mL of purified water was added thereto, the vial was quickly capped, and ultrasonic extraction was performed for 30 minutes. After leaving it at room temperature for more than 48 hours, 0.5 mL of headspace gas in the vial was injected into a gas chromatograph to measure hydrogen. The results are as follows.

[0071] [Table 19]

[0072] It is said that hydrogen water filled in a commercially available aluminum can contains 0.16mg to 0.32mg (0.4ppm to 0.8ppm) of hydrogen per 410ml at the time of shipment. Due to recent technological advances, this amount of hydrogen is considered to be quite large. In contrast, 140 (mL / g) of hydrogen was detected from the first silk hydrogen pearl powder. This corresponds to 12.5mg, so it contains 40 to 78 times more hydrogen than commercially available hydrogen water. In addition, 3.5 (mL / g) of hydrogen was detected from the second silk hydrogen pearl powder. This corresponds to 0.3mg, so it contains almost the same amount of hydrogen as commercially available hydrogen water. This shows that the first silk hydrogen pearl powder according to this embodiment supports an amount of hydrogen that has not been seen before.

[0073] Thus, since "Silk Hydrogen Pearl Powder" has a high hydrogen content, it is expected to have antioxidant, anti-inflammatory, anti-allergic, anti-cancer effects, promote energy production in mitochondria, improve lipid metabolism, improve glucose tolerance, inhibit the onset of arteriosclerosis, and improve symptoms of Parkinson's disease. Furthermore, by mixing it with hydroxyapatite or deep sea water, it is possible to enjoy these benefits.

[0074] [Verification example 22] The present inventors also conducted a "human clinical trial" together with the Japanese Society of Oxidative Therapy Medicine. A human clinical trial was conducted using a hybrid hydrogen supplement that was filled with a mixture of "calcined coral calcium hydrogen powder" as a raw material for generating high-concentration hydrogen ions and "marine mineral hydrogen powder" as a raw material for generating high-concentration hydrogen gas. This "marine mineral hydrogen powder" is a "composite mineral-containing powder" that generates hydrogen gas and hydrogen ions by subjecting deep sea water powder and fine silicon dioxide to hydrogen-carrying processing according to the present embodiment. In this test, as shown in FIG. 7, a statistically significant decrease was observed in the "average values ​​before and five days after ingestion" of the "8-OHdG creatinine ratio," a marker that indicates genetic damage in urine (oxidative stress in the body), within five days after starting to drink. It was found that this is a raw material that fully exerts the penetrating power of hydrogen in a short period of time.

[0075] As described above, according to the present invention, it is possible to provide a method for producing Super Cleanse activated carbon that improves the adsorption properties of carbon and activated carbon, and a method for producing reduced mineral hydrogen powder that can support (adsorb) a large amount of hydrogen. The present invention can be used not only for food applications, but also for cosmetics and miscellaneous goods.

Claims

[Claim 1] A method for producing functional edible charcoal that has a high adsorption function and is edible, A step of setting the pressure in the furnace to 1 to 3 atmospheres and carbonizing vegetation including red pine, bamboo, plum fruit, coconut shells, and phillyraeoides at 500°C to 1500°C; The method includes at least a step of inducing an activation reaction at a temperature of 500°C to 1500°C using "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing with hydrogen, A method for producing functional edible charcoal, wherein the "deep ocean water or water-soluble silicon-containing water" that has been subjected to reduction processing using hydrogen contains liquid water.

Citation Information

Patent Citations

  • Edible charcoal and food product containing the same

    JP2004121238A

  • Health food for inhibiting allergic symptom

    JP2007135495A

  • Charcoal-containing composition

    JP2020068776A

  • Method for producing edible negative hydrogen ions

    JP4404657B2

  • A manufacturing method of the bamboo charcoal that a mineral content is high using deep-ocean water, and a method using the same

    KR1020090097508A